Research Progress of Ponticulus Posticus: A Narrative Literature Review - Xu, Xiaoyan; Zhu, Yuefeng; Ding, Xing; Yin, Mengchen; Mo, Wen; Ma, Junming (Frontiers in Surgery, 2022)
Study Design Narrative review. Objective The purpose of this review was to consolidate the current literature related to ponticulus posticus (PP) and to improve the systematic understanding of this anatomical variant of atlas among spine surgeons. Methods Articles reviewed were searched in PubMed, Ovid MEDLINE, and Embase. All articles of any study design discussing on PP were considered for inclusion. Two independent authors read article titles and abstracts and included appropriate articles. The relevant articles were studied in full text. Results A total of 113 literatures were reviewed and consolidated in this narrative review. These articles are roughly divided into the following five subcategories: (1) epidemiology, (2) pathology and anatomy, (3) clinical presentation, (4) surgical significance, and (5) radiographic examination. Conclusion The PP is non-negligible with a high prevalence. The PP compresses the V3 segment of the artery, the suboccipital nerve, and the venous plexus, consequently contributing to the incidence of neurological pathologies. When a PP is observed or suspected on a lateral radiograph, we recommend that a computed tomography (CT) scan of a patient who is about to receive a C1 lateral mass screw (C1LMS) should be performed, which could determine a safe entry point and the right trajectory of screw insertion.